Association between serum uric acid level and bone mineral density in postmenopausal Iraqi women (Texas Journal of Medical Science, 2023)
Uric acid is the final product of purine metabolism and is synthesized mainly in the liver and intestine, from xanthine, by the action of xanthine oxidoreductase. The serum uric acid concentration is the result of equilibrium among various factors: dietary intake, endogenous synthesis, and renal excretion.